Complete mitochondrial genome of Xiphidiopsis (Xiphidiopsis) gurneyi (Orthoptera, Tettigoniidae, Meconematinae) - Mao, Shao Li (Mitochondrial DNA B Resour, 2018)
Xiphidiopsis (Xiphidiopsis) gurneyi belongs to Meconematinae. The complete mitochondrial genome of X. (X.) gurneyi was sequenced by the next-generation sequencing (NGS) technology. The total length of the mitogenome was 16,225 bp and contains the typical gene arrangement, base composition, codon usage found in Meconematinae species. Phylogenetic tree was constructed based on concatenated datasets of PCGs and rRNAs of X. (X.) gurneyi and 19 Tettigoniidae species to assess their phylogenic relationship. Phylogenetic analysis showed that X. (X.) gurneyi was more closely related to the genus of Xizicus.